Upaya Produktivitas Karya Tulis Mahasiswa di IAIN Tulungagung sebagai Preventif Plagiasi terhadap Qualifed Kalimat Efektif - Wijayanti, Sherina; Zahra, Alifarose Syahda (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
This study focuses on written literacy in form of scientific writing as one of college tridharma. Lack of interest in reading, has attracted the attention of the people to establish literacy communities that aims to spread literacy early on. Someone is able to write scientifically if he/she read a lot of literature such scientific article or journal as an information resources but many people who write without basis by doing plagiarism. This study used library research with descriptive design and literature approach as data collection technique. The results of this research were: 1) Reflections on reading and writing interest, 2) Alternative of plagiarism among students, 3) Recovery of scientific writing in accordance with EYD or EBI rules.